2020
DOI: 10.1101/2020.09.15.20195297
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A co-infection model for Oncogenic HPV and TB with Optimal Control and Cost-Effectiveness Analysis

Abstract: A co-infection model for oncogenic Human papillomavirus (HPV) and Tuberculosis (TB), with optimal control and cost-effectiveness analysis is studied and analyzed to assess the impact of controls against incident infection and against infection with HPV by TB infected individuals as well as optimal TB treatment in reducing the burden of the co-infection of the two diseases in a population. The co-infection model is shown to exhibit the dynamical property of backward bifurcation when the associated reproduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Recent trends in epidemiological research revealed that applying non-integer order differential equations is vital in obtaining good results for dynamical systems. The classical mathematical models of the integer-order derivatives have been greatly employed in studying infectious diseases [10] , [11] , [12] , [13] , [16] , [17] , [18] , [19] , [47] , [27] , [28] , [23] , [24] , [25] . For instance, Omame et al [9] considered and analyzed an integer-order model for the dynamics of Human papillomavirus and Chlamydia trachomatis using optimal control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent trends in epidemiological research revealed that applying non-integer order differential equations is vital in obtaining good results for dynamical systems. The classical mathematical models of the integer-order derivatives have been greatly employed in studying infectious diseases [10] , [11] , [12] , [13] , [16] , [17] , [18] , [19] , [47] , [27] , [28] , [23] , [24] , [25] . For instance, Omame et al [9] considered and analyzed an integer-order model for the dynamics of Human papillomavirus and Chlamydia trachomatis using optimal control.…”
Section: Introductionmentioning
confidence: 99%
“…They examined the impact of various non-pharmaceutical interventions on the control of the disease. In [47] , the authors considered a mathematical model for the co-dynamics of COVID-19 and Dengue in Brazil, with optimal control and cost-effectiveness analysis. Furthermore, Bonyah et al [18] considered and analyzed a mathematical model for the co-infection of dengue fever and Zika virus.…”
Section: Introductionmentioning
confidence: 99%
“…A. Omame et al [16] presented and studied a model of human papillomavirus (HPV) and Chlamydia trachomatis co-infection and showed that trachomatis prevention controls are the most cost-effective strategies to combat HPV and Chlamydia trachomatis co-infections. A. Omamea and D. Okuonghaeb [17] presented a co-infection model for Oncogenic HPV and TB with cost-effectiveness optimal control analysis and showed that the combination of HPV prevention and TB treatment positively impacts the reduction of oncogenic HPV and co-infection.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of mathematical models with different techniques to predict the behavior of epidemics has been increasing [18,93,94]. For example, Farman et al [18] used evolutionary computational techniques and the Padé approach to study a nonlinear model of Hepatitis B.…”
Section: Introductionmentioning
confidence: 99%
“…A. Omame et al [93] introduced and analyzed a model of human papillomavirus (HPV) and Chlamydia trachomatis co-infection, and studied different control strategies to eliminate HPV and Chlamydia trachomatis co-infections. Omame and Okuonghae [94] proposed a co-infection model for oncogenic HPV and tuberculosis with an optimal control analysis and proved that the combination of HPV prevention and tuberculosis treatment has a positive impact on the reduction of oncogenic HPV and co-infection [80].…”
Section: Introductionmentioning
confidence: 99%